EVALUATION OF GROWTH AND YIELD PERFORMANCE ON INOCULATED CHILI PEPPER HYBRIDS BY CUCUMBER MOSAIC VIRUS - Herison, Catur; Handayaningsih, Merakati; Fahrurrozi, Fahrurrozi; Rustikawati, Rustikawati (AGRIVITA Journal of Agricultural Science, 2014)
Tolerance cultivar is a best control measure to reduce losses due to virus attack in the field.  Study on growth and yield of new cultivars compared to the commercial ones is an important step in cultivar development whether they will be accepted by farmers or not. The objective of this research was to study growth and yield of new chili pepper hybrids developed for CMV tolerance in comparison to a commercial and similar fruit size one. Twelve new hybrids and one commercial hybrid cultivar 'Prada', as a control, were evaluated in a completely randomized design with 3 replications. In the greenhouse experiment, H23 and H20 showed better vegetative growth compared to other hybrids and control. Hybrid H17 showed the highest yield followed by H5, H4 and H6.  Keywords.  growth, yield, chili pepper hybrids, CMV tolerance